The Application of Project-Based Learning (PjBL) Models in Learning English for Nursing - sofyan, handayani (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The approach employed was a qualitative, descriptive research method. The research subjects consisted of 41 nursing students enrolled in English for Nursing courses. The data collection method was participant observation. The data analysis was used to describe the results of the simulations and questionnaires. The research findings obtained from participant sheets, questionnaires, and student assignments were analyzed using qualitative descriptive methods to get real data during the implementation of the Project-Based Learning (PjBL) model. From the research results, 85.36% indicated that the Project-Based Learning (PjBL) model used by lecturers in the teaching and learning process helped students better understand every detail in preparing nursing care reports in English, including the appropriate use of vocabulary, term selection, and language structure that must be applied in the field as professional nurses. Meanwhile, the average class score of 77% exceeded the mastery criterion of 70% for the material. This study concludes that the Project-Based Learning (PBL) model is an appropriate learning strategy for the English for Nursing course, providing students with detailed, comprehensive, and challenging learning experiences.